Anti-inflammatory and analgesic activities of solvent fractions of the leaves of Moringa stenopetala Bak. (Moringaceae) in mice models - Yohannes Tamrat; Teshome Nedi; Solomon Assefa; Tilahun Teklehaymanot; Workineh Shibeshi (BMC, 2017)
Abstract Background Many people still experience pain and inflammation regardless of the available drugs for treatments. In addition, the available drugs have many side effects, which necessitated a quest for new drugs from several sources in which medicinal plants are the major one. This study evaluated the analgesic and anti- inflammatory activity of the solvent fractions of Moringa stenopetala in rodent models of pain and inflammation. Methods Successive soxhlet and maceration were used as methods of extractions using solvents of increasing polarity; chloroform, methanol and water. Swiss albino mice models were used in radiant tail flick latency, acetic acid induced writhing and carrageenan induced paw edema to assess the analgesic and anti-inflammatory activities. The test groups received different doses (100 mg/kg, 200 mg/kg and 400 mg/kg) of the three fractions (chloroform, methanol and aqueous). The positive control groups received morphine (20 mg/kg) or aspirin (100 mg/kg or 150 mg/kg) based on the respective models. The negative control groups received the 10 ml/kg of vehicles (distilled water or 2% Tween 80). Results In all models, the chloroform fraction had protections only at a dose of 400 mg/kg. However, the methanol and aqueous fraction at all doses have shown significant central and peripheral analgesic activities with a comparable result to the standards. The aqueous and methanol fractions significantly reduced carrageenan induced inflammation in a dose dependent manner, in which the highest reduction of inflammation was observed in aqueous fraction at 400 mg/kg. Conclusion This study provided evidence on the traditionally claimed uses of the plant in pain and inflammatory diseases, and Moringa stenopetala could be potential source for development of new analgesic and anti-inflammatory drugs.